2014
DOI: 10.17957/jgiass/2.2.496
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Variability in Pea (Pisum Sativum L.)

Abstract: Genetic variability estimation was conducted in twelve genotypes of peas during growing season 2011-12. Analysis of variance was highly significant for all characters studied except plant height present high scope for selection. The highest genotypic and phenotypic co-efficient of variation were recorded for pod per plant (31.62, 31.99) followed by seed yield per plant (22.87, 23.65), cluster per plant (18.81, 20.21) and lowest was noted for days to maturity (1.88, 2.15). High heritability with high genetic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 5 publications
14
4
0
Order By: Relevance
“…Similar findings were also reported by Afreen et al, (2017), Katoch et al, (2016), Jaiswal et al, (2015), Kumar et al, (2015), Ahmad et al, (2014), Asfakun et al, (2013), Kumar et al, (2013) and Pal and Singh (2013). The moderate amount of GCV were recorded for Days to 50% flowering (18.55%), Days to pod setting (18.12%), fibre content (13.33%), pod width (13.28%), number of seeds per pod (12.90%), pod length (12.08%), days to first pod picking (12.06%), number of pods per cluster(9.50%), shelling per cent(9.30%) and seed yield per plant (8.36%).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings were also reported by Afreen et al, (2017), Katoch et al, (2016), Jaiswal et al, (2015), Kumar et al, (2015), Ahmad et al, (2014), Asfakun et al, (2013), Kumar et al, (2013) and Pal and Singh (2013). The moderate amount of GCV were recorded for Days to 50% flowering (18.55%), Days to pod setting (18.12%), fibre content (13.33%), pod width (13.28%), number of seeds per pod (12.90%), pod length (12.08%), days to first pod picking (12.06%), number of pods per cluster(9.50%), shelling per cent(9.30%) and seed yield per plant (8.36%).…”
Section: Resultssupporting
confidence: 86%
“…Similar findings were also reported by Katoch et al, (2016), Jaiswal et al, (2015), Kumar et al, (2015), Ahmad et al, (2014) Asfakun et al, (2013), Kumar et al, (2013) and Pal and Singh (2013).…”
Section: Resultssupporting
confidence: 85%
“…It is also observed that the low range between PCV and GCV so it reveals that these traits have low sensitivity to environmental effects and it is reducible. Similar finding were also reported by Katoch et al, (2016), Siddika et al, (2013), Kumar et al, (2013) and Ahmad et al, (2014).…”
Section: Resultssupporting
confidence: 91%
“…The low amount of PCV were recorded for 100-seed weight (9.27%) followed by pod length (8.96%), seeds per pod(6.42%), plant height (6.10%), yield per plant(4.94%), pod per plant (4.44%), days to maturity (4.03%) and days to 75% flowering. Similar finding were also reported by Katoch et al, (2016), Siddika et al, (2013), Kumar et al, (2013) and Ahmad et al, (2014). GCV measures the amount of variation present in a particular character but it doesn't provide an idea about the proportion of heritable variation present in the total variation therefore, heritability estimates were calculated in the present study.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation